Transcendental Semigroup that has Simply Connected Fatou Components - Subedi, Bishnu Hari (Journal of the Institute of Engineering, 2020)
We prove that there exists non-trivial transcendental semigroup S such that the periodic or pre-periodic or wandering components of Fatou set F(S) have simply connected domain D.